2017
DOI: 10.1073/pnas.1615036114
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of a sulfotransferase for sialic acid-modified glycans mitigates Alzheimer’s pathology

Abstract: We previously showed that microglial keratan sulfate (KS) was induced in amyotrophic lateral sclerosis. However, the functional roles of the glycan and its synthetic enzyme in neurodegenerative diseases, such as Alzheimer's disease (AD), a progressive disorder, are unclear. In our study, KS modified with sialic acids having a molecular mass of 125-220 kDa and the carbohydrate sulfotransferase GlcNAc6ST1 were up-regulated in the brains of two transgenic mouse models (J20 and Tg2576) and the brains of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 53 publications
(76 reference statements)
1
38
0
1
Order By: Relevance
“…Phosphacan is present in early postnatal brains in mice, the 5D4 epitope on KS requires the action of the sulfotransferase GlcNAc6ST1 (Hoshino et al 2014), and this mitigates AD pathology (Zhang et al 2017). GlcNAc6ST1 is up-regulated in the brains of J20 and Tg2576 Tg mice and AD patients correlating with increased levels of 125-190 kDa KSPGs, control tissues however contain > 460-kDa KSPGs (Zhang et al 2017). A better understanding of the cell types that produce these KS species may explain the molecular mechanisms that underlie microglial activation and neurodegenerative processes in AD.…”
Section: Phosphacan/receptor Protein Tyrosine Phosphatase-f and Theirmentioning
confidence: 99%
“…Phosphacan is present in early postnatal brains in mice, the 5D4 epitope on KS requires the action of the sulfotransferase GlcNAc6ST1 (Hoshino et al 2014), and this mitigates AD pathology (Zhang et al 2017). GlcNAc6ST1 is up-regulated in the brains of J20 and Tg2576 Tg mice and AD patients correlating with increased levels of 125-190 kDa KSPGs, control tissues however contain > 460-kDa KSPGs (Zhang et al 2017). A better understanding of the cell types that produce these KS species may explain the molecular mechanisms that underlie microglial activation and neurodegenerative processes in AD.…”
Section: Phosphacan/receptor Protein Tyrosine Phosphatase-f and Theirmentioning
confidence: 99%
“…Another report about the involvement of KS chains in diseases describes modified KS glycans in Alzheimer pathology (Lindahl et al 1996;Zhang et al 2017). The sulfotransferase GlcNAc6ST1 was found to be upregulated in the brains of transgenic mouse models (J20 and Tg2576) and of patients with Alzheimer disease (Zhang et al 2017).…”
Section: Keratan Sulfatementioning
confidence: 97%
“…Another report about the involvement of KS chains in diseases describes modified KS glycans in Alzheimer pathology (Lindahl et al 1996;Zhang et al 2017). The sulfotransferase GlcNAc6ST1 was found to be upregulated in the brains of transgenic mouse models (J20 and Tg2576) and of patients with Alzheimer disease (Zhang et al 2017). KS chains have also been found to play key roles in the early phase of amyotrophic lateral sclerosis (ALS) (Hirano et al 2013), a motor neurondegenerative disease that leads to progressive muscle weakness and complete paralysis within 1 to 5 years after disease onset.…”
Section: Keratan Sulfatementioning
confidence: 99%
“…Also, studies indicated CSF IgG N-glycosylation as a potential biomarker for ALS. Furthermore, a carbohydrate sulfotransferase, GlcNAc6ST1, is upregulated and identified as one of the top 40 ALS relevant genes in microglia [116]. In addition, the concentration of CML, one of the prominent AGEs, significantly elevated in the CSF of ALS patients [117].…”
Section: Glycans and Amyotrophic Lateral Sclerosismentioning
confidence: 99%